DAMPING OF EXPLOSIVE SEISMIC WAVES IN A ROCK BODY - Sadovskiy M.A.; Kostyuchenko V.N. (My University, 1988)
Seismologists usually describe the change in the amplitude of seismic waves with distance R in terms of a power equation such as A =B/Rn. This equation is often used to analyze experimental results on underground explosions. The exponent n and the coefficient B depend on the type of explosion and on the rock properties. The effect of jointing and faults can be identified in a more detailed analysis of the experimental data. With changing scale of the explosion there is a corresponding change in the characteristic size of the joints that govern the damping behavior. As a result, in the near zone, the exponent n generally lies within a small range, from 1.5 to 2, while over a wide range of explosive powers, geometric similarity is preserved, to a first approximation, for the main wave characteristics. At great distances, this similarity does not usually hold. At these distances, the characteristic set of joints and faults typical of the rock body in question plays the key role in damping explosive seismic waves.